Photodynamic Therapy – A Non-invasive Treatment Modality for Precancerous Lesions - Maloth, Kotya Naik; Velpula, Nagalaxmi; Kodangal, Srikanth; Sangmesh, Mithare; Vallamchetla, Kiran; Ugrappa, Sridevi; Meka, Nagajyothi (Journal of Lasers in Medical Sciences, 2016)
Introduction: Oral premalignant lesions are conditions having high potential tendency for transformation into malignancy. The use of a conservative and effective treatment modality is one of the best strategies for cancer prevention. Photodynamic therapy (PDT) is a non-invasive method for topical and selective treatment of oral precancerous lesions. The present study was taken up to determine the efficacy of PDT in oral precancerous lesions. Methods: The study consisted 13 patients with 24 oral leukoplakia (OL) lesions and 8 with 20 oral lichen planus (OLP) lesions, divided into control and study groups. These lesions were affecting various intraoral sites, the buccal mucosa being the most common site followed by tongue and gingiva. The treatment regimen of PDT included 98% 5–aminolevulinic acid (5-ALA) which is topical applied and irradiated with light emitting diode (LED) of 420 nm wavelengths at several sessions. Results: In OL 16.6% of cases showed complete response, 66.6% partial response and 16.6% no response of the lesions to the treatment. In OLP 80% and 20% of the lesions showed partial and no response respectively. The differences with control groups for OL + OLP were found to be significant (P < 0.001). Conclusion: Based on the results of the present study, we can conclude that PDT appears to be a feasible alternative to conventional therapy for oral premalignant lesions.